An evaluation of porcine epidemic diarrhea virus survival in individual feed ingredients in the presence or absence of a liquid antimicrobial. Issue 1 (December 2015) - Dee, Scott; Neill, Casey; Clement, Travis; Singrey, Aaron; Christopher-Hennings, Jane; Nelson, Eric
Abstract Background Contaminated complete feed and porcine plasma are risk factors for PEDV introduction to farms and a liquid antimicrobial has been proven useful for reducing risk. This study provides information on the survivability of PEDV across common swine feed ingredients in the presence or absence of the liquid antimicrobial. Results Eighteen ingredients commonly included in commercial swine diets were selected, including 3 grain sources (corn, soybean meal (SBM), dried distillers grains with solubles (DDGS)), 5 porcine by-products (spray-dried plasma, purified plasma, intestinal mucosa, meat and bone meal and red blood cells (RBCs)), 3 vitamin/trace mineral (VTM) mixes (sow, nursery, finishing), 2 fat sources (choice white grease and soy oil), 3 synthetic amino acids (lysine HCL, D/L methionine, threonine), as well as limestone and dry choline chloride. Complete feed and stock PEDV served as controls. Thirty grams of each ingredient were inoculated with 2 mL PEDV. A matched set of samples were treated with the formaldehyde-based liquid antimicrobial SalCURB® (LA). All samples (n = 320) were stored outdoors under winter time ambient conditions for 30 days. Samples were submitted on 1, 7, 14 and 30 days post-inoculation (DPI) and tested by PCR and virus isolation (VI). All VI-negative samples were tested by swine bioassay. Viable PEDV was detected by VI or swine bioassay at 1, 7, 14 and 30 DPI from SBM, DDGS, meat & bone meal, RBCs, lysine HCL, D/L methionine, choice white grease, choline chloride, complete feed and stock virus control and at 7 DPI in limestone and at 14 DPI in threonine. Supplementary testing of complete feed and SBM indicated viable virus out to 45 and 180 DPI, respectively. All other samples were negative by VI and bioassay. In contrast, treatment with LA inactivated PEDV across all ingredients on 1 DPI and induced RNA reduction over time. Conclusions Under the conditions of this study, PEDV viability in feed was influenced by ingredient with extended survival in SBM. Furthermore, LA treatment rendered virus inactive, independent of ingredient type.